(untitled) (Rome, 2005)
A report of the FAO regional workshop on the elaboration of national plans of action to prevent, deter and eliminate illegal, unreported and unregulated fishing in the Pacific islands subregion.
Keywords: Fisheries,Đánh bắt cá; Islands of the Pacific,Đảo của Thái Bình Dương